Identifikasi Keanekaragaman Flora dan Fauna di Wisata Puncak Harfat Kampung Usaha Jaya Distrik Misool Timur Kabupaten Raja Ampat - Joko, Julianti; Prabawati, Ratna; Sutardi, Sutardi (STKIP HARAPAN BIMA, 2025)
This study aims to identify the level of flora and fauna diversity in the Puncak Harfat tourism area, Kampung Usaha Jaya, East Misool District, Raja Ampat Regency, Southwest Papua. The research employed a mixed-method approach, combining qualitative and quantitative techniques in data collection and analysis. The study was conducted over one month in March 2025, with samples consisting of all flora and fauna found in the eastern part of Puncak Harfat. Data were collected through field observations and interviews, and then analyzed using the Shannon–Wiener Diversity Index, Simpson’s Dominance Index, and Margalef Species Richness Index. The findings revealed 21 species of flora, with orchids and Nepenthes mirabilis identified as dominant species, highlighting the significance of this area as a natural habitat for local flora conservation. For fauna, 15 species were identified, dominated by marine biota such as corals (Acropora, Staghorn Coral) and Amphiprioninae fish, reflecting a diverse ecosystem. The diversity indices of flora (H’ = 2.6721) and fauna (H’ = 2.330) indicate moderate to high categories, while the dominance indices for flora (C = 0.3006) and fauna (C = 0.2655) show no extreme dominance of a single species. Margalef’s richness indices (R = 5.14 and R = 3.44) further confirm the high species richness in the area. Thus, these findings affirm that the Puncak Harfat ecosystem is stable, productive, and suitable to be maintained as a biological conservation site.